(untitled) (TAMADDUN NURI JURNALI, 2024)
The article examines the elements of the speech culture of modern teaching staff, the importance of expressive speech capabilities in their professional activities. Recommendations on the organization of productive professional communication are presented, ways of developing the teacher’s speech culture are considered.